Influence of altiazem pp-180 on hemodynamic parameters in arterial hypertension patients under outpatient conditions (Bangladesh Journal of Medical Science, 2018)
Background: The objective is to study the time-dependent hemodynamic effects of altiazem PP-180 and the blood circulation parameters in patients with arterial hypertension of the II degree in outpatient polyclinic conditions.Methods: The study included 78 patients with essential II grade AH aged 42 to 73 years (mean age of 57.65 ± 0.6). Among them were 28 men and 50 women. The duration of the disease ranged from 4 to 23 years (an average of 9.2 ± 0.12). All the groups involved in the research were divided into two subgroups: the main group and the control group. The control group included 30 patients, who took A-180 once a day at non-fixed hours. The main group included 48 patients, who were divided into random subgroups depending on the time they took A-180 once a day. Within 3 days prior to treatment and during the 10-day treatment course, the medical staff measured all the pateints’ heart rate and blood pressure by NC Korotkoff every 3 hours, 6 times a day. The patients’ heart rate and blood pressure were alternatively self-measured. Prior to treatment and at the end of the 10-day course of therapy with altiazem PP-180, all the patients involved in the research underwent ECG examination and echocardiography on the Aloka machine (Japan).Results: The most favorable hemodynamic support for the hypotensive effect of altiazem PP-180 was observed when patients took it at 7 a.m., 10 a.m. and 10 p.m. in their normal mode of work and rest. When patients took altiazem PP-180 at 1 p.m, 4 p.m. and 7 p.m., its hypotensive effect was due to less favorable hemodynamic support.Conclusions: When taken at different hours of the day - both fixed and non-fixed hours - altiazem PP-180 caused a distinct hypotensive effect in patients with the II degree AH in outpatient polyclinic conditions.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.360-368